2019
DOI: 10.1074/jbc.ra118.006059
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structure of RGS17 suggests a role for Ca2+ in promoting the GTPase-activating protein activity by RZ subfamily members

Abstract: Regulator of G protein signaling (RGS) proteins are negative regulators of G protein–coupled receptor (GPCR) signaling through their ability to act as GTPase-activating proteins (GAPs) for activated Gα subunits. Members of the RZ subfamily of RGS proteins bind to activated Gαo, Gαz, and Gαi1–3 proteins in the nervous system and thereby inhibit downstream pathways, including those involved in Ca2+-dependent signaling. In contrast to other RGS proteins, little is known about RZ subfamily structure and regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…The fragments that do not make contacts with one or more of these four residues could be grown with the intention of reaching these residues and improving their inhibition of the RGS17‐Gα protein‐protein interaction. Evidence to support our findings comes from a recent study that produced the highest resolution crystal structure of RGS17 and identified multiple Ca 2+ binding sites on RGS17 (PDB ID: 6AM3) [33] . Interestingly, one of the identified Ca 2+ binding sites consisted of Y106 and E109, which is near the binding site of fragments 5 – 7 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The fragments that do not make contacts with one or more of these four residues could be grown with the intention of reaching these residues and improving their inhibition of the RGS17‐Gα protein‐protein interaction. Evidence to support our findings comes from a recent study that produced the highest resolution crystal structure of RGS17 and identified multiple Ca 2+ binding sites on RGS17 (PDB ID: 6AM3) [33] . Interestingly, one of the identified Ca 2+ binding sites consisted of Y106 and E109, which is near the binding site of fragments 5 – 7 .…”
Section: Discussionsupporting
confidence: 85%
“…Evidence to support our findings comes from a recent study that produced the highest resolution crystal structure of RGS17 and identified multiple Ca 2 + binding sites on RGS17 (PDB ID: 6AM3). [33] Interestingly, one of the identified Ca 2 + binding sites consisted of Y106 and E109, which is near the binding site of fragments 5-7. The study found that Ca 2 + promoted the RGS17-Gα interaction and improved the catalytic efficiency of GTP-hydrolysis by Gα bound to RGS17.…”
Section: Discussionmentioning
confidence: 97%
“…Another way to achieve selectivity for small molecules is to elucidate RGS structural information at the atomic level. For example, a recent report by Seing et al presented a 1.5 Å crystal structure of RGS17, the highest-resolution crystal structure for an RZ family member to date, that revealed novel Ca 2ϩ -binding sites (119). Expanding upon this initial discovery, Seing et al went on to discover that Ca 2ϩ binding positively regulates RGS17 GAP activity.…”
Section: Compound Selectivitymentioning
confidence: 99%